Microbial assessment of commercial pet foods marketed in the United Arab Emirates - Hadid, Michella; Alwan, Nisreen; Dimassi, Hani; Deghel, Maria; El Khatib, Sami; Serhan, Mireille; Hassan, Hussein F. (Frontiers in Veterinary Science, 2024)
Examining the microbiological characteristics of pet food is imperative to safeguard the health and well-being of companion animals, pet owners, and the surrounding environment. Domestic animals, known for carrying harmful microorganisms, pose a significant health risk, especially in close proximity to people and children. Notably, no studies have previously investigated pet food quality in the Gulf Cooperation Council countries, in particular, the United Arab Emirates (UAE). This study examined the microbiological quality of all stock keeping units (SKUs) of pet foods marketed in UAE (n=118).Parameters assessed include Total Aerobic Microbial Count (TAMC), Enterobacteriaceae, Total Yeast and Mold Count (TYMC), Salmonella, Listeria monocytogenes, and Clostridium species. Among the 118 samples, 33 (28%) exceeded the acceptable TAMC limit of 10 6 CFU/g, highlighting significant variations based on manufacturers and ingredients. Eight samples (7%) surpassed the maximum Enterobacteriaceae limit of 3 x 10 2 CFU/g. TYMC levels exhibited variation, with 33 (28%) exceeding the limit of 10 4 CFU/g. ListeriaL. monocytogenes was identified in 44 (37%) of the samples, while Salmonella was not detected. Clostridium contamination was observed in 28 (24%) of the samples. Statistical analyses revealed associations between pet food characteristics and microbial quality, underscoring the imperative for international standards to ensure the safety of pet food. These findings carry significant implications for pet owners, regulatory bodies, and the pet food industry, emphasizing the need for ongoing efforts to enhance the overall quality and safety of pet food products.